HUKUM LELANG OBYEK HAK TANGGUNGAN TERHADAP HARTA BERSAMA SETELAH PERCERAIAN TANPA PERSETUJUAN ISTRI PUTUSAN No: 25 PK/Pdt/2019 - Pupimbiddi Nasution (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
Decision Number: 25 PK/Pdt/2019 which is a re-examination of Decision Number: 222 K/Pdt/2017 which determines Zainul Arifin as the winner of the mortgage auction where in the implementation of the credit agreement and binding the mortgage there is an unlawful act where the object of the mortgage is joint property which in its implementation there is no agreement from either side of the wife, but the judge's decision ratifies the object of dispute in the auction that is carried out. So that it raises the question of how the legal provisions provide guarantees for joint assets that are carried out after a divorce that does not share joint assets. How is the validity of the Auction of Mortgage Objects for Joint Assets where one of the parties is not regulated according to laws and regulations. What is the law on the judge's consideration in decision No: 25 PK/Pdt/2019 regarding the auction of mortgage objects carried out by the husband without the wife's consent. Which was finally entitled